DARI NALAR FIKIH MENUJU NALAR UNDANG-UNDANG (TRANSFORMASI HUKUM ISLAM KE DALAM LEGISLASI NASIONAL) - Marzuki, Marzuki (State Institute of Islamic Studies (IAIN) Palu, 2006)
It is not easy to make a definition of â€œlawâ€ since Islamic syariâ€™ah, Islamic law and fiqh areÂ law in nature. Basically, in a society, law aims at serving and protecting society. It is a system of implementation to protect both individual rights and societal rights. Besides, it possesses nature and scope of its own. Law is constant. It is not influenced by room and time. It is only Muslimâ€™s interpretation to the law that always changes in accordance with socio-historical and cultural spheres. Islamic syariâ€™ah, Islam law and fiqh, lie on the argument used. Islamic syariâ€™ah is based on the Qurâ€™an and the Sunnah without any legal reasoning, but constantly relies on the spirit of the two Islamic sources. So, Islamic syariâ€™ah is constant while Islamic law is temporal. In the context of positive law, Islamic law has good prospect as long as law practitioners are capable of optimizing the strength and opportunity possessed by Islamic law.Â Â Â Â Kata Kunci: Â Undang-undang, syariâ€™ah, hukum Islam